Perhitungan Nilai Cadangan Premi Tahunan Asuransi Jiwa Dwiguna Menggunakan Metode New Jersey dan Fackler - Yulita, Tiara (Indonesian Journal of Applied Mathematics, 2025)
Endowment life insurance is a type of life insurance that involves two types of benefits, namely the company will provide compensation if the insured remains alive at the end of the policy term or dies during the policy term. Premium reserves are the amount of funds that must be available to the insurance company as funds for preparing claim payments to the insured. The aim of this research is to calculate the annual premium reserve value in one of the assumed cases of Company XYZ with a coverage period of 35 years and a premium payment period of 20 years. Calculation of premium reserves can be done using a prospective and retrospective approach. The New Jersey method is included in one of the prospective premium reserve calculation methods which is an improvement and more effective than the Illinois method, with a minimum premium payment of 20 payments. The Fackler method is a calculation with a retrospective approach. The results of calculating premium reserves using the New Jersey and Fackler methods increase every year and have the same value. The results of these calculations show that the insurance company has sufficient funds to fulfill its obligations to the insured.